HAK PILIH BAGI PENYANDANG DISABILITAS PADA PELAKSANAAN PEMILU TAHUN 2024(Studi Kasus TPS 003 Desa Semparuk Kecamatan Semparuk Kabupaten Sambas) - GADIS RIZIKA; Nilhakim Nilhakim; Miswinda Miswinda (JOURNAL OF LAW AND NATION, 2025)
General elections are a form of people's sovereignty, but their implementation is often not fully inclusive. Although laws and regulations in Indonesia have ensured equal political rights for persons with disabilities, implementation on the ground still shows gaps. This phenomenon can be seen in the 2024 election in Semporuk Village, where a number of people with disabilities are unable to exercise their voting rights due to various obstacles. The formulation of the problem in this study is: 1) How to fulfill the right to vote for people with disabilities in the implementation of the 2024 Election in Semparuk Village, Semparuk District, Sambas Regency and 2) What are the obstacles faced in fulfilling political rights for people with disabilities in the implementation of the 2024 Election in Semparuk Village, Semparuk District, Sambas Regency. This study uses a type of qualitative research with an empirical juridical approach to examine the gap between the rule of law and practice in society. Primary data sources were obtained through in-depth interviews with people with disabilities, village officials, Voting Committees (PPS), and Voting Organizing Groups (KPPS), as well as through direct observation at polling stations. Secondary data comes from laws and regulations, books, and scientific journals. The results of the study show that the fulfillment of political rights for people with disabilities in Semparuk Village is only limited to procedural formalities and fails substantively. Their right to be registered in the DPT is indeed fulfilled, but in its implementation, they face serious obstacles such as access to polling stations that are not disability-friendly, the principle of vote confidentiality that is sacrificed due to incomplete tools, and the absence of accessible socialization. The main obstacle found is institutional (systemic), which is rooted in the failure of election organizers. These obstacles include inaccurate data on voters with disabilities, inadequate officer training, and the absence of a special budget for accessible polling stations. This constraint is exacerbated by sociological factors such as stigma in society and individual factors such as mobility barriers which are a direct impact of system failures.